Upaya Meningkatkan Pelayanan Kepolisian Melalui Sentra Pelayanan Kepolisian Terpadu (SPKT) (Studi Pada Polisi Resort Pasuruan Kota) - Krisna Anggun Pratiwi (Jurnal Administrasi Publik, 2015)
Abstract: Efforts To Improve The Quality Of Police Service Unit Police Service Center (SPKT) Integrated Police Resort Pasuruan City.            Research methodology that is used is descriptive research with a qualitative approach to the location of research on Police Resorts Pasuruan City. To the source of primary data obtained through interviews with the source of information and secondary data in the form of the regulation. The results of research shows that efforts to improve the quality of police service unit police service center (SPKT) integrated Police Resort Pasuruan City can be conducted based on regulations as the basis of service, police resources, and infrastructure. The quality of services that traditional integrated police service center unit (SPKT) Police Resort Pasuruan City can be said to have met the standards and the service excellence service determined by the existence of effective, efficient, fast, right, open, and cheap viewed from the type of service, standard time of service, the cost of services, the age of the reporter, and procedures. Supporters and inhibitors of factors seen from two terms and the internal factor is the internal factor. Improvements need to be increased and, in terms of operational budget police personnel, and infrastructure, but the police service center (SPKT) integrated Police Resort Pasuruan City keeps trying to provide qualified public service pasuruan to create city convenience and orderliness in society. Keywords: efforts to improve services, Integrated Police Service Center Abstrak: Upaya Meningkatkan Kualitas Pelayanan Kepolisian Unit Sentra Pelayanan Kepolisian Terpadu (SPKT) Polres Pasuruan Kota. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Dengan sumber data primer yang diperoleh melalui wawancara dengan narasumber dan data sekunder yaitu berupa peraturan yang berlaku. Hasil dari penelitian menunjukkan bahwa upaya meningkatkan kualitas dapat dilakukan dengan berpedoman pada regulasi sebagai dasar, sumber daya, dan sarana prasarana. Kualitas pelayanan yang disuguhkan dapat dikatakan telah memenuhi standar dan prinsip pelayanan yang ditentukan dengan adanya pelayanan yang efektif, efisien, cepat, tepat, terbuka, dan murah dilihat dari segi jenis pelayanan, standar waktu pelayanan, biaya pelayanan, usia pelapor, dan prosedur pelayanan. Faktor pendukung dan penghambat dilihat dari dua segi yaitu faktor internal dan faktor internal. Diperlukan adanya peningkatan dan perbaikan dalam segi anggaran operasional, personel, dan sarana prasarana, namun terus berupaya untuk memberikan pelayanan yang berkualitas kepada masyarakat agar tercipta ketentraman dan ketertiban di lingkungan masyarakat.   Kata kunci: pelayanan kepolisian, Sentra Pelayanan Kepolisian Terpadu